2019
DOI: 10.1371/journal.pone.0217486
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of cervical high-risk human papillomavirus infection mostly covered by Gardasil-9 prophylactic vaccine in adult women living in N’Djamena, Chad

Abstract: Background We conducted in 2018 a descriptive, quantitative, population-based, cross-sectional survey estimating the prevalence of cervical high-risk human papillomavirus (HR-HPV) infection and associated risk factors among adult women living in N’Djamena, Chad. Methods Five of the 10 districts of N’Djamena were randomly selected for inclusion. Peer educators contacted adult women in community-churches or women association networks to participate in the survey and come … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 54 publications
5
19
0
Order By: Relevance
“…Out of a sample of 278 women enrolled, the mean age (37 years) mainly represents the most sexually active population and therefore having chronic exposure to sexually transmitted infections, including HPV. These results are similar to those obtained in Cameroon with Kabayene et al(mean age of 38.5 years) and in Chad (mean age of 35 years) (12,17,18).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Out of a sample of 278 women enrolled, the mean age (37 years) mainly represents the most sexually active population and therefore having chronic exposure to sexually transmitted infections, including HPV. These results are similar to those obtained in Cameroon with Kabayene et al(mean age of 38.5 years) and in Chad (mean age of 35 years) (12,17,18).…”
Section: Discussionsupporting
confidence: 92%
“…As reported by Kevin A. Ault in 2006, High-risk, oncogenic HPV types (including HPV 16 and HPV 18) are associated with 99.7% of all cervical cancers (11). A recent study conducted in Chad during the year 2018 showed that 11 genotypes of HR-HPV were detected in nearly 70% of the study population, and HR-HPV 58 genotype was the most prevalent (22.9%) (12). In Cameroon, out of 14,000 new cases of cancer reported in 2016, cervical cancer occupied the second leading position of cancers among women (23.2%) (12,13).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Direct consequences are clinical manifestations of HPV-associated dysplasia, which has been recognized in early HIV epidemics (10). As reported by Kevin A. Ault in 2006, High-risk, oncogenic HPV types (including HPV 16 and HPV 18) are associated with 99.7% of all cervical cancers (11). A recent study conducted in Chad during the year 2018 showed that 11 genotypes of HR-HPV were detected in nearly 70% of the study population, and HR-HPV 58 genotype was the most prevalent (22.9%) (12).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that contribute to HPV infections include: early sexual activity, multiple sexual partners, immunocompromised (HIV essentially), smoking, and prolonged oral contraception [8]. Thus, the primary prevention of cervical cancer by vaccinating girls aged 9 to 14 years with one of the 3 available vaccines (Cervarix, Gardasil-4 or Gardasil-9) before they begin sexual intercourse would theoretically protect them against most HR-HPV infections [9,10]. This primary prevention, combined with other prevention strategies (secondary and tertiary prevention) already in place in SSA, would be the ideal equation to overcome the high burden of cervical cancer on this continent [11,12].…”
Section: Introductionmentioning
confidence: 99%